Analysis of symmetrical pulse width modulation strategies for matrix converters - Larsen, K.B.; Jorgensen, A.H.; Helle, L.; Blaabjerg, F. (IEEE 33rd Annual Power Electronics Specialists Conference 2002, 2002)
This paper presents a new and easy way to understand the derivation of the modulation functions for matrix converters. It is shown how the duty cycles can be calculated using techniques known from the back-to-back (B2B) voltage source inverter (VSI), thus making the subject accessible to people with prior knowledge in standard drives. A new modulation strategy is presented minimizing harmonic distortion compared to the standard double-sided space vector modulation for matrix converters. An improvement to an existing modulator is also presented where the proposed modification improves the harmonic performance. The strategies are compared both analytically and by the use of both simulations and measurements on a 12 kW matrix converter prototype. It is found that the proposed modulator has superior performance compared to modulators with equal switching frequencies and an equal number of switchings.